2014
DOI: 10.1136/bmjopen-2014-005290
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a behaviour change intervention on the diets and physical activity levels of women attending Sure Start Children’s Centres: results from a complex public health intervention

Abstract: ObjectivesThe UK government's response to the obesity epidemic calls for action in communities to improve people's health behaviour. This study evaluated the effects of a community intervention on dietary quality and levels of physical activity of women from disadvantaged backgrounds.DesignNon-randomised controlled evaluation of a complex public health intervention.Participants527 women attending Sure Start Children's Centres (SSCC) in Southampton (intervention) and 495 women attending SSCCs in Gosport and Hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…These changes were still apparent one year after training [56]. Evaluation showed that women who came into contact with trained staff had significantly smaller declines in their sense of control and self-efficacy than women in the control group, although an effect on diet was not observed [57]. Self-efficacy and sense of control are psychological factors known to be associated with diet quality among disadvantaged women.…”
Section: Interventionsmentioning
confidence: 99%
“…These changes were still apparent one year after training [56]. Evaluation showed that women who came into contact with trained staff had significantly smaller declines in their sense of control and self-efficacy than women in the control group, although an effect on diet was not observed [57]. Self-efficacy and sense of control are psychological factors known to be associated with diet quality among disadvantaged women.…”
Section: Interventionsmentioning
confidence: 99%
“…Fortunately, the available literature also suggests that these kinds of barriers can be overcome. DOHaD-related concepts have been successfully translated to several hard-to-reach, albeit selected, populations with low levels of health literacy (adolescents in New Zealand and the Cook Islands, adolescents in Uganda, and low SEP women in the United Kingdom; Baird et al, 2014;Bay et al, 2012, 2016a, Bay, Morton, & Vickers, 2016b, Bay, Vickers, Mora, SLoboda, & Morton, 2017a, Bay et al, 2017bMacNab & Mukisa, 2017;Barker et al, 2017). In these selected cohorts, knowledge translation has required development of hands-on curricula and/or deep engagement and cultivation of meaningful relationships with community partners but is proving fruitful (Grace & Bay, 2011;MacNab & Mukisa, 2017).…”
Section: Inequity In Who Has Dohad Knowledgementioning
confidence: 99%
“…Changes to the way staff worked were still evident a year post-training [30]. A non-randomised controlled trial of the effect of exposure to trained staff on diet and physical activity levels in women attending SSCCs showed that the intervention had no measurable effect on women’s diet and physical activity levels, but that it may have protected against a decline in their self-efficacy and perceptions of control over life, factors known to be associated with change in both these health behaviours [31]. …”
Section: The Southampton Initiative For Healthmentioning
confidence: 99%